Early Coronary Artery Disease in a Female Patient with Discoid Lupus Erythematosus and Hashimoto’s Thyroiditis - Dimitrovska, Biljana; Jovchevska, Simona; Bede, I.; Vraynko, Elif; Kostova, Nela; Zafirovska Taleska, Biljana; Otljanska, Magdalena (Scientific Foundation SPIROSKI, 2023)
BACKGROUND: Atherosclerosis is a chronic inflammatory condition involving the endothelium of the blood vessels, predominant the coronary arteries. Main risk factors are dyslipidemia, hypertension, diabetes, smoking, obesity, and lack of physical activity.  Patients  with autoimmune diseases, including rheumatoid arthritis, systemic lupus erythematosus, systemic sclerosis etc., have a twofold increased risk of developing CAD at younger age, compared with the general population. CASE REPORT: A 41-year-old female patient, with history of smoking and dyslipidemia, was admitted to our hospital with acute inferoposterior myocardial infarction. Initially, coronary reperfusion therapy per protocol was administrated and primary percutaneous coronary intervention (PCI) was performed. Multivessel CAD was found, and two stents were implanted on obtuse marginal and circumflex artery. Transthoracic echocardiography (TTE)  revealed left ventricle systolic and diastolic dysfunction with segmental hypokinesis. Additionally, the patient was first diagnosed with DLE at the age of  15, but the disease was uncontrolled in the last 7 years. She also has hypothyroidism, regularly treated with hormone replacement therapy. The  patient was discharged with medicamentous therapy including dual antiplatelet agents, statin, beta-blocker, angiotensin-receptor blocker, potassium sparing diuretic and proton pump inhibitor. One month later, recoronarography was performed with stenting of left anterior descending artery. TTE showed improvement of the left ventricle systolic function with preserved ejection fraction. The blood test showed elevated levels of antithyroid antibodies. A rheumatologist was consulted, who recommended therapy with hydroxychloroquine and regular follow-ups. CONCLUSION: In younger patients with chronic inflammatory diseases, inflammatory mediators play a significant role in the development of the  atherosclerotic plaques, regardless of co-existing risk factors. Therefore, an early cardiovascular assessment is required in these patients for preventing severe or life-threatening cardiovascular events.